Comparative in vitro characterization of moxidectin and doramectin percutaneous absorption through bovine skin - Sallovitz, Juan Manuel (2012)
Topical formulations have achieved worldwide acceptance in veterinary medicine because their administration is an easy, less labor-intensive and nonstressing form. Any chemical compound that comes in contact with the skin has the potential to be locally and⁄or systemically absorbed. However, many factors related to the features of animal skin, composition of the topical formulation and to the drug itself can determine marked differences in the percutaneous absorption process. The aim of the current work was to characterize the pattern of in vitro percutaneous absorption for moxidectin (MXD) and doramectin (DRM), two of the most worldwide used topical macrocyclic lactone antiparasitic compounds in cattle. The work included the development of a simple and inexpensive in vitro assay useful to predict in vivo drug percutaneous absorption in cattle. Both drugs were administered as the commercial formulations intended for their topical administration to cattle. The in vitro studies were carried out using modiﬁed Franz-type vertical diffusion cells. Cattle skin slices of 500 lm thickness were prepared using a dermatome to separate the stratum corneum and upper epidermis from dermis and subcutaneous tissue. The receptor medium was sampled up to 72 h postadministration and drug concentrations were measured by HPLC. The parameters used to estimate the comparative in vitro skin permeation showed marked differences between DRM and MXD. A 5.29-fold longer lag time (Tlag) was observed for DRM. Similarly, the ﬂux (J) (2.93-fold) and the permeation coefﬁcients (Kp ) (2.95-fold) in cattle skin were signiﬁcantly higher (P < 0.05) for DRM compared to those obtained for MXD. Additionally, the data obtained from the in vitro permeation studies was correlated with the plasma concentrations of both compounds achieved in vivo in cattle treated with the same topical formulations. Correlation coefﬁcients between percentage of drug permeated in vitro vs. percentage of drug absorbed in vivo (up to 48 h posttreatment) were 0.856?0.887 (MXD) and 0.976?0.990 (DRM). However, the highestin vitro?in vivo correlations for both molecules were observed up to 24 h post-treatment A rapid screening method for testing different topical formulations can be achieved with the simple in vitro cattle skin permeation technique described here, which has been successfully adapted to test the comparative percutaneous absorption of MXD and DRM.